Art as a Means of Propaganda: Accounting for a Hierarchical Set - Kazim Tolga Gürel (Sortuz)
Art which is the description of the relation between the subject and object from an aesthetical   point of view is used to create a classified society and then to protect the life principles of the dominant group-bourgeoisie- and to create symbolic set between the dominant class and other classes. Although this symbolic classification structure was harmed in the postmodern era, this determination is still valid. Besides it is used as means for propaganda, it also carries on its function of creating a set for classification. With the composing of popular culture and reproduction of artistic indicators, and with the loss of uniqueness, the use of artistic activities as a meta caused the deconstruction of its function as a set for classification. The astounding development of the propaganda means in the modern times led to the popularization of the art and in this process of popularization the nature of art also changed. Within this context and within the scope of this study, propaganda will be defined and the classification relations of art will be handled before this set causing nature of propaganda is studied.